Parkinson's disease-associated 18 bp promoter variant of DJ-1 alters REST binding and regulates its expression. (31st January 2023) - Pal, Prosenjit; Roy, Shubhrajit; Chowdhury, Abhishek; Chatterjee, Raghunath; Ray, Kunal; Ray, Jharna
Highlights: Eighteen base pair (g.168_185) deletion allele of DJ-1 promoter is a risk factor for aged PD patients in eastern India. The expression of DJ-1 is observed to be significantly reduced in the presence of both deletion and duplication variants. REST, a transcription factor, can bind to the 18 bp insertion sequence of DJ-1 promoter and regulates its expression. An 18 bp deletion or, duplication of DJ-1 promoter results in the loss of REST binding which compromises DJ-1 expression. Abstract: Parkinson's disease (PD) is a progressive neurodegenerative disorder with a complex etiology. Presence of autosomal mutations in PARK7/DJ-1 gene has been associated with early-onset PD. Growing evidence has suggested that DJ-1 acts as a putative sensor of oxidative stress. Reduced levels of DJ-1 protein have been reported in the cerebrospinal fluid of sporadic PD patients. Several case-control association studies have identified DJ-1  g.168_185del (rs200968609) variants conferring susceptibility towards PD pathogenesis. Similarly, among the PD patients in eastern India, the deletion allele (g.168_185) of this DJ-1 promoter polymorphism was found to be associated with PD. Hence, we aimed to find out the functional contribution of this promoter variant of DJ-1 in PD pathogenesis. The expression of DJ-1 was observed to be significantly reduced in the presence of both deletion and duplication sequences as identified from the luciferase promoter activity assay. The transcription factor binding prediction tool identified DJ-1 promoter 18 bp insertion polymorphism as the only binding partner of REST (RE1 Silencing Transcription Factor). Transient Chromatin Immuno-precipitation (ChIP) assay further confirmed this prediction. Previous reports have highlighted the role of REST in regulating the expression of stress-responsive genes. Our study has identified the functional involvement of DJ-1 promoter variants and REST-mediated regulation of DJ-1 expression in PD pathogenesis.